URIC ACID LEVELS CORRELATES WITH INFLAMMATORY MARKERS AND ADHESION MOLECULES IN HEMODIALYSIS PATIENTS - Julie Calixto Lobo; Antonio Claudio Lucas; da Nóbrega; José Carlos Carraro-Eduardo; Denise Mafra (The Korean Society of Nephrology, 2012)
Elevated serum uric acid has been associated to a variety of cardiovascular disease states and with systemic inflammation. The aim of this study was to analyze the association between uric acid levels and inflammatory markers in hemodialysis (HD) patients. This cross-sectional study included 50 HD patients (62% men, 54.3±12.6 yrs, BMI 24.4±4 Kg/m2) and 21 healthy individuals (45% men, 50.7±15.7 yrs, BMI 25.5±4.0 Kg/m2). Uric acid was measured using uricase-PAP method, inflammatory (TNF-α, IL-6 and CRP) and atherosclerosis markers (ICAM-1, VCAM-1, MCP-1 and PAI-1) were measured by a multiplexed particle-based flow cytometric assay. There was a positive correlation between serum uric acid and inflammatory markers, IL-6 (r=0.30, p=0.01), CRP (r=0.37, p=0.003), TNF-α (r=0.40, p=0.001) and adhesion molecules levels, ICAM-1 (r=0.53, p=0.0001), and VCAM-1 (r=0.45, p=0.0001) Parameters HD Patients Healthy individuals CRP (mg/mL) 0.32 ± 0.30* 0.11 ± 0.12 TNF-α (pg/mL) 5.5 ± 2.1* 2.4 ± 1.1 IL-6 (pg/mL) 4.1 ± 1.6* 2.7 ± 0.4 PAI-1 (ng/mL) 7.0 ± 2.7 6.2 ± 2.1 MCP-1 (pg/ml) 47.6 ± 24.2 37.3 ± 19.0 VCAM-1 (ng/mL) 48.5 ± 8.5* 23.8 ± 5.5 ICAM-1 (ng/mL) 20.5 ± 15.9* 7.2 ± 1.2⁎p<0.05 In conclusion, these original data suggest that uric acid may have a role in inflammation and atherosclerosis in HD patients